ABOUT THE LOCALIZATION OF DZHETYKENT IN THE TERRITORY OF SOUTH KAZAKHSTAN - Kozha, М.Б.; Junisbayev, А.; Zhanaltay, Ж. (Journal of Oriental Studies, 2025)
The article discusses the issues of localization of the historical region of Dzhetykent, often recorded in historical writings and documents and with which a number of important events of the Middle Ages and modern times in the history of the peoples of Central Asia and Kazakhstan were associated. The article aims to identify, and analysis all known reports about Dzhetykent in historical sources that spatially and chronologically linking the long-forgotten toponym to a specific region of Central Asia. Medieval written sources, Russian maps and documents of modern times of the 18th–19th centuries, data from the historical memory of the inhabitants of the region, recorded by Ch.Ch. Valikhanov, Shadi-tore, Mailykozha, Kazangap Bayboluly, Russian researchers of the 19th – early 20th centuries, including the data from the traveler M. Pospelov’s map of 1800 were analyzed in the article. Based on an analysis of sources in Central Asia, we can scientifically identify two areas where “seven towns or villages” were located and were known in the sources as Dzhetykent. The first Dzhetykent was in Eastern Fergana, the second is localized on the territory of Southern Kazakhstan in the Arys-Badam interfluve. South Kazakhstan Dzhetykent included: Shymkent, Sairam, Mankent, Karabulak, Karamurt, Sultanrabat, Zhangaktyk. An assumption has been made that the toponym is mentioned by the Chinese author of the 7th century as a principality with «a hundred cities», as well as in the Iranian chronicle of the 17th century on how the region of «thousands of cities and villages» corresponds to Jettikent in Russian and Kazakh sources of the 18th – early 20th centuries. Keywords: Historical geography, Central Asia, Dzhetykend, Sairam, Shymkent, map of M. Pospelov 1800.